Different interpretations of terrorism in international relations theory : approaches of Turkey and Russia to the concept of terrorism and the ISIS case - Dybovskaia, Elizaveta (My University, 2021)
Bu tezin amacı, Türkiye ve Rusya’nın terörizm konusundaki resmi tanımlamalarını incelemek ve bu iki ülkenin terörizm kavramına yaklaşımlarını uluslararası ilişkiler teorilerinin perspektifinden açıklamaktır. Bu amaçla tezde terörizm kavramına ilişkin teorik tartışmalar Uluslararası İlişkiler’in dört ana teorisi olan neorealizm, neoliberalizm, neo-Marksizm ve konstrüktivizm açısından ele alınmakta ve ayrıca IŞİD vakası üzerinden Rusya ve Türkiye’nin terörizmle ilgili yaklaşımları ve politikaları irdelenmektedir. Rusya’nın ve Türkiye’nin terörizmle ilgili yaklaşımlarının analizi sonucunda Rusya’nın bu konuya daha çok iç ve dış politikalarını meşrulaştırmak için bir düşman imajı inşa etmek amacıyla yaklaştığı, Türkiye’nin ise meseleyi mevcut devlet sistemini, hükümeti ve ulusal çıkarları koruma üzerinden değerlendirdiğini ortaya çıkmaktadır. Diğer bir deyişle Rusya’nın terörizm konusuna yaklaşımı daha çok konstrüktivist teori çerçevesinde ele alınabilecek iken, Türkiye’nin yaklaşımını neorealist teori yardımıyla açıklamak mümkündür. Genel olarak ise Rusya ve Türkiye’nin terörizm kavramına yaklaşımlarının anlaşılması, bu iki ülkenin günümüzde bu konuda izlemekte oldukları politikaların daha iyi açıklanabilmesi için önemlidir.

The aim of this thesis is to examine the official definitions of terrorism in Russia and Turkey and explain their approaches to the understanding and interpretation of the concept of terrorism within the framework of the theory of international relations (IR). To this end, the thesis includes an overview of the theoretical discussions surrounding the phenomenon of terrorism from the perspective of four main IR theories, namely neorealism, neoliberalism, neo-Marxism and constructivism as well as the analysis of the Russian and the Turkish positions and policies on terrorism using the Islamic States of Iraq and Syria (ISIS) as a case study. The analysis of the Russian and Turkish interpretations of terrorism provides significant evidence that the Russian approach to the concept of terrorism aims to construct an enemy image in order to legitimize the domestic and foreign policies of Russia, while the Turkish approach is much more focused on protecting the existing state system as well as the government and national interests of Turkey. In other words, Russia’s approach to terrorism fits more into the framework of the constructivist IR theory, whereas Turkey’s position could be rather explained through the neorealist IR theory. All in all, the understanding of Russia and Turkey’s perceptions about terrorism is important for explaining the current policies of these countries on terrorism-related issues.
Keywords: constructivism; International relations; ISIS; IŞİD; konstrüktivizm; neorealism; neorealizm; Political science; Russia; Rusya; Siyasal bilim; Terörizm; Terrorism; Turkey; Türkiye; Uluslararası ilişkiler